Kreasi Seni Sebagai Daya Tarik Wisata Budaya di Padepokan Bagong Kussudiarja Yogyakarta - Yulianto Yulianto (Media Wisata, 2015)
Yogyakarta is a city of education and cultural city, as well as tourist areas, are still waking life order of the society and various art and cultural activities are still maintained their authenticity. Art creations that there in hermitage is one of the cultural heritage, both in the form of classical dance, dance creations, Ballet, theatre, art and others which are the legacy of the Bagong Kussudiardja. The research method used is descriptive qualitative research with data collection techniques derived from primary data is information obtained from primary sources and secondary data is data capture techniques through observation, interview, documentation and literature. Some of the art creations in Bagong Kussudiardja is one of the artists to create and store a variety of works that made some of the Bagong Kussudiardja one of the Cultural Attractions in Yogyakarta. Art creations are in hermitage : jagongan wagen, estuary, angjasana, edukreasi, fine art, among the classical dance, sedulur Ballet, dance, dances and other activities is a form of art and cultural works with the aim that the some of the Bagong Kussudiadrja is one of the cultural heritage in Yogyakarta and Indonesia